ANALISIS PRODUKSI PENDAPATAN USAHA TANI BERAS KETAN DI DESA BUMI AGUNG WATES KECAMATAN BAHUGA KABUPATEN WAY KANAN - Sugeng Supriyanto (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2017)
The objectives of this research are to: 1) Know the management of glutinous rice farming, 2) Knowing the revenues of sticky rice. The results showed that the glutinous rice cultivation in the village of Bumi Agung Wates Bahuga District Way Kanan Regency more profitable. The average income earned by glutinous rice farmers is Rp. 20,537,636 per hectare per year.